"Men Are Scared That Others Will Know and Will Discriminate Against Them So They Would Rather Not Start Treatment." Perceptions of Heterosexual Men on HIV-Related Stigma in HIV Services in Blantyre, Malawi. (December 2021) - Kazuma-Matululu, Thokozani; Nyondo-Mipando, Alinane Linda
Background: Although the concept of treatment as prevention has generated optimism that an AIDS-free generation is within reach, the success of this approach centers upon early diagnosis and linkages to care for people living with HIV. Unfortunately, people continue to present for HIV care at late stages of disease and HIV-related stigma has been recognized as the major impediment to HIV prevention and treatment efforts. Given the relevance of addressing stigma to improve access and utilization of HIV services among men, this secondary analysis assessed perceptions of heterosexual men in HIV-related stigma on HIV testing and ART services in Blantyre District. Methods: Purposive sampling was done with maximum variation which included men with unknown statuses, newly diagnosed with HIV infection and not yet on ARVs and those with HIV infection on ART. These participants were varied according to age and area of residency and included men from urban, semi urban and rural areas. Health care workers were included depending in the participation in the provision of HIV services. Eighteen (18 IDIs) and sixteen (16) KIIs were done at private facilities and a total of twenty (20) IDS and seventeen (17) KIIs interviews were conducted at public facilities and fourteen (14) FGD were conducted at public facilities as well. The data were collected from January to July 2017 and March to September 2018. Results: Men perceived that there are barriers and enablers that influence men from accessing HIV testing and ART services. These factors include individuals, family, community and workplace. The surroundings can be a person, community and a family and it plays an integral part in ones' decision to get tested or initiate on ART. At all these levels, men would navigate the options of accessing the services while risking stigma and discrimination. Conclusion: HIV-related stigma exists and impedes access to HIV testing and ART services in men. Men preferred private hospitals to public facilities because of their ability to maintain respect to privacy and confidentiality to their client's. Imitating these policies into the public hospitals can help to improve the perception of HIV-related stigma in heterosexual men.